Shoo, caveflies! - Stilton, Geronimo (Stilton, Geronimo. Cavemice, 2017)
When their cousin is stung by a cavefly and falls into a deep sleep, Geronimo and Thea set out in search of the rare pink stinkrose, whose petals are thought to provide a cure.